Carcass merit traits: development of EPDS for Warner-Bratzler shear force and DNA marker validation - Pollak, E.J.; Lipsey, R.J.; Westcott, E.A.; Dikeman, Michael E.; Stroda, Sally L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Warner-Bratzler shear force data on strip loin steaks were obtained on 761 steers from contemporary groups of progeny from the most popular 38 Simmental sires, and 133 steers from nine Simbrah sires. The range for Warner-Bratzler shear force EPDs for the Simmental sires was from -0.51 lb (more tender) to +0.48 lb (less tender). The range in EPDs for the Simbrah sires was from -0.73 to +0.73 lb. In addition, DNA analyses and screening have been completed for 11 quantitative trait loci on several Simmental and Simbrah sires. Information from this project should allow cattle producers to improve carcass traits, tenderness, and other palatability traits through classical genetic selection or through DNA marker-assisted selection.
Keywords: Beef; EPDs; Warner-Bratzler shear force; DNA marker; Carcass merit traits